2021
DOI: 10.1016/j.frl.2020.101745
|View full text |Cite
|
Sign up to set email alerts
|

Market reactions to the arrival and containment of COVID-19: An event study

Abstract: Highlights We investigate short-term stock market reactions during the COVID-19 pandemic Stocks react significantly negatively to the announcement of the first death Stock markets react negatively to country-specific fiscal policy measures Monetary measures have the power to calm markets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
139
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(171 citation statements)
references
References 32 publications
8
139
1
8
Order By: Relevance
“…Another associated category of research that assesses government action's influence on the stock market includes (Ashraf, 2020;Baig et al, 2021;Gao et al, 2021;Heyden & Heyden, 2020;Narayan et al, 2021). Ashraf (2020) describes that the government announcements of social distancing have a negative effect on stock market returns due to their adverse effect on economic activity, while an indirect positive effect through the reduction in COVID-19 confirmed cases using data across 77 countries.…”
Section: Pandemic and Financial Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another associated category of research that assesses government action's influence on the stock market includes (Ashraf, 2020;Baig et al, 2021;Gao et al, 2021;Heyden & Heyden, 2020;Narayan et al, 2021). Ashraf (2020) describes that the government announcements of social distancing have a negative effect on stock market returns due to their adverse effect on economic activity, while an indirect positive effect through the reduction in COVID-19 confirmed cases using data across 77 countries.…”
Section: Pandemic and Financial Marketsmentioning
confidence: 99%
“…Ashraf (2020) describes that the government announcements of social distancing have a negative effect on stock market returns due to their adverse effect on economic activity, while an indirect positive effect through the reduction in COVID-19 confirmed cases using data across 77 countries. Heyden and Heyden (2020) study the short-term market reactions of U.S. and European stocks at the beginning of the COVID-19 pandemic. Authors conclude that stock returns respond negatively to the declarations of the country-specific fiscal policy measures, whereas market calm in response to the monetary policy measures.…”
Section: Pandemic and Financial Marketsmentioning
confidence: 99%
“…Mazur et al ( 9 ) explored the stock market performances in the United States during the pandemic and found that the stock prices in natural gas, food, healthcare, and software industries showed an upward trend, while the stock prices in oil, real estate, entertainment, and hotel industries showed the opposite. Heyden and Heyden ( 10 ) studied the short-term reaction in stock markets of the United States and Europe at the early stage of the pandemic. Their results showed that fiscal measures had a negative impact on stock returns, while monetary policy had a stabilizing effect on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Although the analysis is provided from the macro aspect, i.e., national stock market indices are observed, a first glance will be given in the reactions of the CESEE markets. However, such markets are characterized by less liquid stocks [40], which could be exploited in studies such as [41] where 867 companies were included in the study. The main purpose of this study was to evaluate the magnitude of the negative effects of COVID-19 on selected CESEE markets and to obtain information about trading possibilities based on the results.…”
Section: Introductionmentioning
confidence: 99%